Authorship in studies conducted in low-and-middle income countries and published by Reproductive Health: advancing equitable global health research collaborations - Pingray, Verónica (2020)
Reproductive Health has an interest in reproductivehealth status globally, but it has particular interest inphenomena affecting disadvantaged populations. This isthe reason why this journal encourages submissionsfrom researchers conducting studies in low- and middleincome countries (LMICs).